(9分之1-6分之1-18分之1)*(负36)=9分之1-6分之1-18分之1*(-36)=9分之1-6分之1+2=18
1个回答
这样解答不对
9分之1-6分之1-18分之1)*(负36)
=9分之1*(-36)-6分之1*(-36)-18分之1*(-36)
=-4+6+2
=4
相关问题
(9分之1+6分之1-18分之1)乘36+怎么算
-36分之1/[-9分之1+12分之1-18分之1+36分之1
(-36)×(4分之1-6分之5+9分之7-18分之1); 怎么写,
把2分之1,3分之1,6分之1,9分之1,9分之2,9分之4,9分之5,18分之5,18分之7填入9个格子里,转下面
36分之1÷(4分之1+12分之1-18分之7-36分之1)+(4分之1+12分之1-18分之7-36分之1)÷36分之
100×(-3)×(-5)×0.01 (9分之6-6分之1-18分之1)×36 (4分之1-2分之1-8分之1)×128
(9分之4+6分之5-18分之7)36分之1 能简便就简便
9分之3 12分之4 18分之6 2分之1 4分之1 8分之1 16分之1
(4分之1-6分之5+9分之7-18分之1)×(-72)=
2*4分之1*4*6分之1*6*8分之1+.+16*18分之1+18*20分之1